Transmission of Methicillin‐Resistant Staphylococcus aureus via Deceased Donor Liver Transplantation Confirmed by Whole Genome Sequencing. Issue 11 (22nd September 2014) - Altman, D. R.; Sebra, R.; Hand, J.; Attie, O.; Deikus, G.; Carpini, K. W. D.; Patel, G.; Rana, M.; Arvelakis, A.; Grewal, P.; Dutta, J.; Rose, H.; et al.
<x xml:space="preserve">Abstract</x> Donor‐derived bacterial infection is a recognized complication of solid organ transplantation (SOT). The present report describes the clinical details and successful outcome in a liver transplant recipient despite transmission of methicillin‐resistant Staphylococcus aureus (MRSA) from a deceased donor with MRSA endocarditis and bacteremia. We further describe whole genome sequencing (WGS) and complete de novo assembly of the donor and recipient MRSA isolate genomes, which confirms that both isolates are genetically 100% identical. We propose that similar application of WGS techniques to future investigations of donor bacterial transmission would strengthen the definition of proven bacterial transmission in SOT, particularly in the presence of highly clonal bacteria such as MRSA. WGS will further improve our understanding of the epidemiology of bacterial transmission in SOT and the risk of adverse patient outcomes when it occurs.